Fluorinated Paramagnetic Complexes: Sensitive and Responsive Probes for Magnetic Resonance Spectroscopy and Imaging - Peterson, Katie L.; Srivastava, Kriti; Pierre, Valérie C. (Frontiers in Chemistry, 2018)
Fluorine magnetic resonance spectroscopy (MRS) and magnetic resonance imaging (MRI) of chemical and physiological processes is becoming more widespread. The strength of this technique comes from the negligible background signal in in vivo 19F MRI and the large chemical shift window of 19F that enables it to image concomitantly more than one marker. These same advantages have also been successfully exploited in the design of responsive 19F probes. Part of the recent growth of this technique can be attributed to novel designs of 19F probes with improved imaging parameters due to the incorporation of paramagnetic metal ions. In this review, we provide a description of the theories and strategies that have been employed successfully to improve the sensitivity of 19F probes with paramagnetic metal ions. The Bloch-Wangsness-Redfield theory accurately predicts how molecular parameters such as distance, geometry, rotational correlation times, as well as the nature, oxidation state, and spin state of the metal ion affect the sensitivity of the fluorine-based probes. The principles governing the design of responsive 19F probes are subsequently described in a “how to” guide format. Examples of such probes and their advantages and disadvantages are highlighted through a synopsis of the literature.